1979
DOI: 10.1136/thx.34.6.801
|View full text |Cite
|
Sign up to set email alerts
|

Use of BCG as an immunostimulant after resection of carcinoma of the lung: a two-year assessment of a trial of 500 patients.

Abstract: BCG (Glaxo) (0 5 ml =5 X 106 organisms) was given subdermally to 250 patients ten days after resection of a lung carcinoma to stimulate the immune system. Increased activity of lymphocytes and macrophages could possibly result in the destruction of small extrapulmonary tumour deposits that were previously unidentified. The two-year survival of this group of patients was compared with 250 controls not receiving BCG after operation. A comparative analysis of the sex, histological types, and lymph node involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…For example, in a consecutive series of 245 patients undergoing curative resection, Wilkins et al (1978) reported 5-year survival rates of 42% in patients without mediastinal node involvement compared with only 16% with such involvement. Greschuchna and Maassen (1980) reported corresponding rates of 37% and 11%, and broadly similar results were reported by others (Edwards, 1979;Mountain, 1986).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…For example, in a consecutive series of 245 patients undergoing curative resection, Wilkins et al (1978) reported 5-year survival rates of 42% in patients without mediastinal node involvement compared with only 16% with such involvement. Greschuchna and Maassen (1980) reported corresponding rates of 37% and 11%, and broadly similar results were reported by others (Edwards, 1979;Mountain, 1986).…”
supporting
confidence: 88%
“…For example, in a consecutive series of 245 patients undergoing curative resection, Wilkins et al (1978) reported 5-year survival rates of 42% in patients without mediastinal node involvement compared with only 16% with such involvement. Greschuchna and Maassen (1980) reported corresponding rates of 37% and 11%, and broadly similar results were reported by others (Edwards, 1979;Mountain, 1986).Secondly, the importance of careful preoperative staging in the selection of patients suitable for intended resection was appreciated, particularly the need to avoid inappropriate thoracotomy in patients with T3 tumours, gross mediastinal node involvement or metastatic disease (Pearson, 1980;Spiro and Goldstraw, 1984). This need can only be met if, in patients otherwise suitable for thoracotomy, the mediastinum is staged, using such techniques as computerised tomography (CT), cervical mediastinoscopy and anterior mediastinotomy (if so indicated for left upper lobe tumours), and if clinical…”
supporting
confidence: 86%
“…Despite attempts to advance early diagnosis and the use of many combination chemotherapy regimens, including immunotherapy using bacillus Calmette-Gue脗 rin, interferons, IL-2, and allogenic tumor extracts (Edwards 1979;Figlin and Sarna 1983;Ardizzoni et al 1994;Hollinshead 1987), for patients with inoperable tumors, the clinical response and prognosis of adenocarcinoma is still poor. The autocrine secretion of growth factors can be a central mechanism in the process of malignant transformation (Bergh 1990), and it has been reported that proliferation of lung cancer is regulated by several growth factors such as transforming growth factor b (Pelton and Moses 1990) and epidermal growth factor (Garcia et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The overall five-year survival in all 90 patients was 37 %, favourable prognostic features being squamous carcinoma (45 % five-year survival) as opposed to undifferentiated carcinoma (27%); and lobectomy (45 %) rather than pneumonectomy (28 %). When 14 (54%Y) Five-year results of a controlled study of BCG immunotherapy after surgical resectioti routinely biopsied mediastinal nodes were free of tumour the overall five-year survival was 460% but even when these nodes were positive 190% patients survived five years. When the intradermal and multipuncture groups are considered together as an 'immunotherapy" group and compared directly with the control group, no significant difference could be demonstrated in the various subgroups of patients (table 2).…”
Section: Resultsmentioning
confidence: 99%